2019
DOI: 10.3390/pr8010005
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide/Chitosan Magnetic Nanocomposite Immobilized Manganese Peroxidase for Decolorization of Textile Wastewater

Abstract: Because of its effectiveness in organic pollutant degradation, manganese peroxidase (MnP) enzyme has attracted significant attention in recent years regarding its use for wastewater treatment. Herein, MnP was extracted from Anthracophyllum discolor fungi and immobilized on the surface of magnetic nanocomposite Fe 3 O 4 /chitosan. The prepared nanocomposite offered a high surface area for MnP immobilization. The influence of several environmental factors like temperature, pH, as well as storage duration on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 54 publications
(60 reference statements)
2
43
0
Order By: Relevance
“…The highest dye removal was achieved at a pH of four. According to the results, the dyes were degraded using Reusability is an important economic factor for determining the cost of the water treatment process [47,48]. In addition, reusability determines the applicability of the materials in industrial water treatment.…”
Section: The Effect Of Ph On Removal Efficienciesmentioning
confidence: 99%
“…The highest dye removal was achieved at a pH of four. According to the results, the dyes were degraded using Reusability is an important economic factor for determining the cost of the water treatment process [47,48]. In addition, reusability determines the applicability of the materials in industrial water treatment.…”
Section: The Effect Of Ph On Removal Efficienciesmentioning
confidence: 99%
“…Besides the type of immobilized enzymes, the dye degradation process plays an important role in the support material. Siddeeg et al [53] showed a role of applied support in enzyme immobilization and application in removal of dyes. They prepared nanocomposite from chitosan and Fe 3 O 4 nanoparticles covered by N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride, characterized by a high surface area, suitable for manganese peroxidase attachment.…”
Section: Removal Of Dyesmentioning
confidence: 99%
“…Firstly, the magnetic chitosan was prepared via the co-precipitation method as described in our previous work [31]. Briefly, two oxidation states of iron (FeCl 3 and FeSO 4 solutions) were mixed in a conical flask in 2:1 molar ratios, respectively, followed by the dropwise addition of aqueous ammonia (33%, v/v) accompanied by vigorous stirring under a nitrogen atmosphere for 30 min.…”
Section: Polypyrrole Magnetic Chitosan Synthesismentioning
confidence: 99%